2011
DOI: 10.1002/cjce.20480
|View full text |Cite
|
Sign up to set email alerts
|

Performance properties of acrylic and acrylic polyol–polyurethane based hybrid system via addition of nano‐caco3 and nanoclay

Abstract: Thermosetting acrylic (TSA) resin was prepared by solution polymerisation of acrylic acid and methyl methacrylate (MMA). Hybrid polymer consisting of acrylic polyol-polyurethane was prepared by addition of hydroxy ethyl acrylate and hexamethylene diisocyanate (HMDI). Incorporation of Functionalised nanocalcium carbonate and bentonite nanoclay were accomplished by in situ method during the synthesis of both the polymers. Loading of nano-CaCO 3 and nanoclay was varied from 0 to 4 wt.% to investigate variation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Hybrid materials combine the constituents aiming for a synergy leading to properties exceeding those of the individual constituents. Nanosized clay and calcium carbonate particles have been used in polymer nanocomposites enhancing, for example, abrasion resistance (Mishra et al 2005;Subramani et al 2007;Kapole et al 2011). A few studies report structures combining cellulose and clay particles suggested for, among others, packaging (Tunc and Duman 2010), thermoplastic composites (Ludvik et al 2007;Delhom et al 2010) and to improve thermal properties (Cerruti et al 2008;Lin et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Hybrid materials combine the constituents aiming for a synergy leading to properties exceeding those of the individual constituents. Nanosized clay and calcium carbonate particles have been used in polymer nanocomposites enhancing, for example, abrasion resistance (Mishra et al 2005;Subramani et al 2007;Kapole et al 2011). A few studies report structures combining cellulose and clay particles suggested for, among others, packaging (Tunc and Duman 2010), thermoplastic composites (Ludvik et al 2007;Delhom et al 2010) and to improve thermal properties (Cerruti et al 2008;Lin et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…For instance, the palm‐based acrylic polyol ester resin could be used as a UV curable coating 8. The hybrid polymer coating film of acrylic polyol/hexamethylene diisocyanate (HDI)/nano‐CaCO 3 had improved its gloss, pencil hardness, abrasion resistance 9…”
Section: Introductionmentioning
confidence: 99%